1991
DOI: 10.1038/clpt.1991.104
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to nicotinic acid flushing

Abstract: The mechanism of tolerance to nicotinic acid flushing was determined in subjects during a 5-day course of treatment. Objective measures of skin blood flow were used to confirm the development of tolerance. Plasma levels of nicotinic acid showed marked intraindividual variability but were not decreased with the development of tolerance. However plasma levels of 9-alpha 11-beta prostaglandin F2, a stable metabolite of prostaglandin D2, became undetectable in most subjects with the development of tolerance. Thus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 0 publications
2
38
1
Order By: Relevance
“…Carlson and Oro ( 17 ) found that niacin lowered the arterial plasma concentration of FFAs in fasting humans within minutes. This effect is dose dependent ( 20 ) and is not desensitized after 6 months of regular treatment ( 21 ), in contrast with niacin's fl ushing effect which undergoes tachyphylaxis within a week ( 22 ). This suppression of plasma FFAs reduced the supply of substrate for the hepatic synthesis of TGs, VLDL and LDL particles ( 23 ).…”
Section: Effect On Ldl and Vldlmentioning
confidence: 99%
See 1 more Smart Citation
“…Carlson and Oro ( 17 ) found that niacin lowered the arterial plasma concentration of FFAs in fasting humans within minutes. This effect is dose dependent ( 20 ) and is not desensitized after 6 months of regular treatment ( 21 ), in contrast with niacin's fl ushing effect which undergoes tachyphylaxis within a week ( 22 ). This suppression of plasma FFAs reduced the supply of substrate for the hepatic synthesis of TGs, VLDL and LDL particles ( 23 ).…”
Section: Effect On Ldl and Vldlmentioning
confidence: 99%
“…During chronic drug administration, niacin-induced fl ushing and prostaglandin release are subject to tachyphylaxis within a week ( 22,75 ).…”
Section: Effects On Hdlmentioning
confidence: 99%
“…Intriguingly, these acute effects decrease upon prolonged niacin treatment. Adipocyte lipolysis normalizes ( 15,16 ) and fl ushing diminishes ( 17 ).…”
Section: Quantitative Pcrmentioning
confidence: 99%
“…However, it has now been well established that both methyl nicotinate and nicotinic acid-induced flushing response is the result of increased prostaglandin synthesis in skin cells, suggested to be macrophages or adipocytes, which then act upon capillary epithelial cells to cause vasodilation (Wilkin et al, 1982(Wilkin et al, , 1985Morrow et al, 1989;Turenne et al, 2001). Interestingly, healthy subjects develop tolerance to the nicotinic acid-induced flushing response (Stern et al, 1991). This appears to be due to diminished prostaglandin D 2 synthesis, which has been implicated as the main prostaglandin subtype responsible for nicotinic acid-induced vasodilation (Morrow et al, 1989).…”
Section: Discussionmentioning
confidence: 99%